Manajemen dan Pemberdayaan Manusia untuk Mengefektifkan Organisasi di SMAN 1 Laubaleng, Kabupaten Karo, Sumatera Utara - Ribka Hernita Sitepu; Petrus Sanjaya Simarmata; Hilmi Saputri Nasution; Aman Simaremare; Ibnu Hajar (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
This study aims to describe human management and empowerment to streamline the organization at SMA N 1 Laubaleng, Karo Regency, North Sumatra. That the success of the school managed by the principal is a manifestation of efforts to develop a school organization based on creativity and innovation. This research was conducted with a descriptive qualitative approach. The use of these methods and approaches is in accordance with the main objectives of the study, namely reviewing, describing, analyzing data, and information according to the needs in this context related to management and human empowerment to Streamline the organization at SMA N 1 Laubaleng. Data collection through interviews, observations, document analysis and literature studies. The results showed, that SMA N 1 Laubaleng as a learning organization can be understood as an organization that continuously transforms itself to manage knowledge, use technology, empower society, and expand learning, to adapt and achieve better success in an ever-changing environment, and the importance of the process takes place decisively and collectively.